Interaction of Molybdo-Phosphoric and Molybdo-Antimono-Phosphoric Heteropoly Acids with Silica Gels Modified with Aliphatic and Heterocyclic Quaternary Ammonium Salts - Olga A. Zaporozhets; Igor A. Kachan; Lionel S. Zinko; Julia P. Bas; Valentyn I. Davydov (Adsorption Science & Technology)
The interaction of molybdo-phosphoric and molybdo-antimonophosphoric heteropoly acids with aliphatic (tetradecylammonium nitrate and trinonyloctadecylammonium iodide) and heterocyclic (lucigenine and safranine) quaternary ammonium salts immobilized onto silica has been studied using adsorption and spectroscopic methods. It has been shown that the formation of ionassociates between the quaternary ammonium cations and the heteropoly anions is accompanied by their interaction with surface silica groups which accounts for the tight binding of heteropoly acids to the surface. Such interfacial reactions can successfully be applied to the development of spectroscopic and semi-quantitative visual test techniques for detecting trace amounts of phosphorus and antimony.